LANGUAGE AS A COMMUNICATION TOOL IN HUMAN LIFE - Apriyanto apriyanto (Fox Justi : Jurnal Ilmu Hukum, 2020)
Humans need communication to help survival, one of which is by using language as a means of communication. Language is the most effective communication tool in conveying messages, thoughts, feelings, goals to others and allows for creating cooperation between humans. So that the role of language becomes very dominant in various human daily activities. The purpose of this study is to describe matters relating to language as a means of communication and communication in everyday life. The method used in this research is the literature review method, the data is collected from relevant literature data. The result of this research and discussion is to explain about language as a communication tool which discusses the function of language as a human communication tool which includes five basic functions, namely the function of expression, the function of information, the function of exploration, the function of persuasion, and the function of entertainment. And explain about communication in everyday life which discusses why we communicate and the language used when communicating in everyday life. As social beings, of course humans in their lives need communication to be able to establish relationships with other humans. Language is the most effective tool or medium for conveying thoughts, with human language being able to interact and talk about anything.